Comparison of enzymatic activities and proteomic profiles of Butyrivibrio fibrisolvens grown on different carbon sources - Sechovcová, Hana; Kulhavá, Lucie; Fliegerová, Kateřina; Trundová, Mária; Morais, Daniel; Mrázek, Jakub; Kopečný, Jan (Proteome science, 2019)
Background: The rumen microbiota is one of the most complex consortia of anaerobes, involving archaea, bacteria, protozoa, fungi and phages. They are very effective at utilizing plant polysaccharides, especially cellulose and hemicelluloses. The most important hemicellulose decomposers are clustered with the genus Butyrivibrio. As the related species differ in their range of hydrolytic activities and substrate preferences, Butyrivibrio fibrisolvens was selected as one of the most effective isolates and thus suitable for proteomic studies on substrate comparisons in the extracellular fraction. The B. fibrisolvens genome is the biggest in the butyrivibria cluster and is focused on "environmental information processing" and "carbohydrate metabolism". Methods: The study of the effect of carbon source on B. fibrisolvens 3071 was based on cultures grown on four substrates: xylose, glucose, xylan, xylan with 25% glucose. The enzymatic activities were studied by spectrophotometric and zymogram methods. Proteomic study was based on genomics, 2D electrophoresis and nLC/MS (Bruker Daltonics) analysis. Results: Extracellular β-endoxylanase as well as xylan β-xylosidase activities were induced with xylan. The presence of the xylan polymer induced hemicellulolytic enzymes and increased the protein fraction in the interval from 40 to 80 kDa. 2D electrophoresis with nLC/MS analysis of extracellular B. fibrisolvens 3071 proteins found 14 diverse proteins with significantly different expression on the tested substrates. Conclusion: The comparison of four carbon sources resulted in the main significant changes in B. fibrisolvens proteome occurring outside the fibrolytic cluster of proteins. The affected proteins mainly belonged to the glycolysis and protein synthesis cluster.